The influence of recycling number on the mechanical, chemical, thermal and rheological properties of poly(butylene terephthalate)/polycarbonate binary blend and glass-fibre-reinforced composite - Kuram, Emel; Ozcelik, Babur; Yilmaz, Faruk (SAGE PUBLICATIONS LTD, 2016)
Poly(butylene terephthalate)/polycarbonate (PBT/PC) binary blend was reprocessed by repeated injection moulding process to explore whether recycling is possible for this polymer blend. In the current study, PBT/PC blends were reprocessed until five processing cycles and the mechanical, chemical, thermal, and rheological properties of recycled PBT/PC blends were evaluated after each reprocessing cycle. The recycling of the glass-fibre-reinforced PBT/PC composites was also investigated in this study. From the experimental results, it was concluded that recycled glass-fibre-reinforced PBT/PC (PBT/PC-GF) composites showed better mechanical properties in comparison to virgin PBT/PC binary blends and fifth recycled PBT/PC-GF composite could be used instead of virgin PBT/PC. It was also found that PBT/PC binary blend was a suitable material for the recycling process and this polymer blend did not suffer any significant deterioration.
Keywords: PBT; PC; polymer blends; glass-fibres; mechanical properties; injection moulding; recycling; DIMENSIONAL STABILITY; REPROCESSING CYCLES; FRACTURE-BEHAVIOR; VIRGIN; PARTICLES; NANOCOMPOSITES; MORPHOLOGY; STRENGTH; Materials Science